Killer or helper? The mechanism underlying the role of adenylate activated kinase in sound conditioning - Zhao, Rui; Ma, Changhong; Wang, Minjun; Li, Xinxin; Liu, Wei; Shi, Lin; Yu, Ning (Frontiers in Synaptic Neuroscience, 2022)
Objective To investigate whether sound conditioning influences auditory system protection by activating adenylate activated kinase (AMPK), and if such adaption protects ribbon synapses from high-intensity noise exposure. Materials and methods CBA mice (12 weeks old) were randomly divided into four groups (n = 24 mice per group): control, sound conditioning (SC), sound conditioning plus noise exposure (SC+NE), and noise exposure (NE). Hearing thresholds were assessed before testing, after sound conditioning, and 0, 3, 7, and 14 days after 110 dB noise exposure. Amplitudes and latencies of wave I at 90 dB intensity were assessed before test, after conditioning, and at 0 and 14 days after 110 dB noise exposure. One cochlea from each mouse was subjected to immunofluorescence staining to assess synapse numbers and AMPK activation, while the other cochlea was analyzed for phosphorylated adenylate activated kinase (p-AMPK) protein expression by western blot. Results There was no significant difference in auditory brainstem response (ABR) threshold between SC and control mice. The degree of hearing loss of animals in the two SC groups was significantly reduced compared to the NE group after 110 dB noise exposure. Animals in the SC group showed faster recovery to normal thresholds, and 65 dB SPL sound conditioning had a stronger auditory protection effect. After sound conditioning, the amplitude of ABR I wave in the SC group was higher than that in the control group. Immediately after noise exposure (D0), the amplitudes of ABR I wave decreased significantly in all groups; the most significant decrease was in the NE group, with amplitude in 65SC+NE group significantly higher than that in the 85SC+NE group. Wave I latency in the SC group was significantly shorter than that in the control group. At D0, latency was prolonged in the NE group compared with the control group. In contrast, there was no significant difference in latency between the 65SC+NE and 85SC+NE groups. Further, at D14, there was no significant difference between the NE and control groups, while latency remained significantly shorter in the 65SC+NE and 85SC+NE groups compared with controls. Number of ribbon synapses in SC mice did not differ significantly from that in controls. After 110 dB noise exposure, there were significantly more ribbon synapses in the SC+NE group than the NE group. Ribbon synapses of all groups were recovered 14 days after the noise exposure, while the SC group had a shorter recovery time than the non-SC groups (p < 0.05). AMPK was highly activated in the SC group, and p-AMPK expression was detected; however, after 110 dB noise exposure, the strongest protein expression was detected in the NE group, followed by the SC+NE groups, and the lowest protein expression was detected in the control group. Conclusion Sound conditioning animals were more noise resistant and recovered hearing faster than non-SC animals. Further, 65 dB SPL SC offered better hearing protection than 85 dB SPL SC. Early AMPK activation may protect hearing by increasing ATP storage and reducing the release of large quantities of p-AMPK, which could help to inhibit synapse damage.